2011
DOI: 10.1101/gad.17288211
|View full text |Cite
|
Sign up to set email alerts
|

Compaction of chromatin by diverse Polycomb group proteins requires localized regions of high charge

Abstract: Polycomb group (PcG) proteins are required for the epigenetic maintenance of developmental genes in a silent state. Proteins in the Polycomb-repressive complex 1 (PRC1) class of the PcG are conserved from flies to humans and inhibit transcription. One hypothesis for PRC1 mechanism is that it compacts chromatin, based in part on electron microscopy experiments demonstrating that Drosophila PRC1 compacts nucleosomal arrays. We show that this function is conserved between Drosophila and mouse PRC1 complexes and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
237
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(255 citation statements)
references
References 64 publications
18
237
0
Order By: Relevance
“…The C-terminal regions (CTRs) of Su(z)2 and Psc have been considered the core of these proteins as they are the main contributors of PRC1-mediated silencing; they can, on their own, recapitulate the inhibition of chromatin remodeling, compaction of chromatin, and transcriptional repression exhibited by PRC1 in vitro (King et al 2002(King et al , 2005Francis et al 2004;Lo et al 2009;Beh et al 2012). This is consistent with the fact that, while the mammalian orthologs do not have the CTR, the function of the CTR has been retained in mammals in a stretch of positively charged residues found in the Pc subunit of the PRC1 (Grau et al 2011). Thus, it is believed that the HR serves as the hub of protein-protein interactions which, in part, help direct the CTR to genomic regions requiring regulation by PcG proteins.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…The C-terminal regions (CTRs) of Su(z)2 and Psc have been considered the core of these proteins as they are the main contributors of PRC1-mediated silencing; they can, on their own, recapitulate the inhibition of chromatin remodeling, compaction of chromatin, and transcriptional repression exhibited by PRC1 in vitro (King et al 2002(King et al , 2005Francis et al 2004;Lo et al 2009;Beh et al 2012). This is consistent with the fact that, while the mammalian orthologs do not have the CTR, the function of the CTR has been retained in mammals in a stretch of positively charged residues found in the Pc subunit of the PRC1 (Grau et al 2011). Thus, it is believed that the HR serves as the hub of protein-protein interactions which, in part, help direct the CTR to genomic regions requiring regulation by PcG proteins.…”
supporting
confidence: 69%
“…Our findings may also explain the absence of a CTR among the mammalian homologs of Su(z)2, Bmi-1, and Mel-18 (Brunk et al 1991;van Lohuizen et al 1991;Grau et al 2011;Beh et al 2012), as it is possible that mammalian HRs have evolved in such a way as to compensate for the absence of a CTR. On the other hand, it may be that the CTR function of chromatin compaction, first discovered with Drosophila proteins in vitro (Francis et al 2004), still exists in mammals but is found within a different PcG member, M33/ Cbx2 (Grau et al 2011).…”
Section: Potential Mechanisms Of Su(z)2 Regulationmentioning
confidence: 77%
See 2 more Smart Citations
“…Proteins of the Polycomb group, regulate and interact with epigenetic marks, controlling gene expression programs through cell divisions (Schwartz and Pirrotta, 2008). It has been shown that Polycomb-repressive complexes mediate chromatin compaction in flies and mice (Grau et al, 2011). This largescale chromatin change represses the expression of many developmental genes (Isono et al, 2005;Boyer et al, 2006;Lee et al, 2006;Lanzuolo et al, 2007;Sing et al, 2009).…”
Section: The Unknown Spatial Distribution Of Cis-regulatory Informationmentioning
confidence: 99%